2009
DOI: 10.1159/000235802
|View full text |Cite
|
Sign up to set email alerts
|

Blind Verification of Elevated Platelet Autoantibodies in Serum of Schizophrenic Patients – Part II: Adult Subjects

Abstract: Background: In our preceding study, we assayed in a blind fashion the blood sera of young normal subjects and schizophrenic patients for levels of platelet autoantibodies (PAA). The recorded PAA titers of the schizophrenic patients were significantly higher than those of the normal subjects. This observation has lent support to this test being used as an objective evaluation of schizophrenia in young subjects in the future. In addition, this finding strongly suggested that the etiology of a distinct group of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 70 publications
0
10
2
Order By: Relevance
“…It has been previously reported that the serum of schizophrenia patients is enriched with PAA [4,6,10,11] and an inverse correlation has been detected between the duration of disease and the level of PAA titers [10,11,16]. The main objective of the present study was to assess the impact of clozapine and nonclozapine antipsychotics on PAA levels in COS patients and to evaluate a possible relationship between clinical improvement and alterations in PAA levels.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been previously reported that the serum of schizophrenia patients is enriched with PAA [4,6,10,11] and an inverse correlation has been detected between the duration of disease and the level of PAA titers [10,11,16]. The main objective of the present study was to assess the impact of clozapine and nonclozapine antipsychotics on PAA levels in COS patients and to evaluate a possible relationship between clinical improvement and alterations in PAA levels.…”
Section: Discussionmentioning
confidence: 95%
“…A procedure outlined in our previous publications [9,10,11] was used. Ten milliliters of venous blood was collected from each of the participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A procedure outlined in our previous publications [9,10,11] was used. Twenty milliliters of venous blood were drawn from each of the participants and then evaluated at the laboratory at the Weizmann Institute.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated significantly higher blood titers of PAA in adult schizophrenia patients as compared to normal healthy subjects [4,5,6]. In addition, young schizophrenia patients at their early stages of the disorder displayed higher PAA titers than older patients with longer duration of the disorder [9,10,11]. …”
Section: Introductionmentioning
confidence: 99%